Exploring the past, present, and future of the mindfulness field: A multitechnique bibliometric review - Bunjak, Aldijana; Černe, Matej; Schölly, Emilie Lara (Frontiers in Psychology, 2022)
This paper provides an overview of the mindfulness literature up until the end of 2020 by (a) uncovering its underlying intellectual structure, (b) identifying the most influential and popular themes, and (c) presenting new directions for future research on mindfulness. To this end, a systematic quantitative review based on bibliometric methods was conducted, which is perhaps less prone to researcher bias and can complement existing meta-analyses and qualitative (narrative) structured reviews as an objective approach. Three bibliometric techniques – document co-citation analysis, co-word (co-occurrence and content) analysis, and bibliographic coupling – were applied to explore the past, present, and future of mindfulness research. The co-citation analysis showed that measurement, mechanisms, mindfulness-based interventions, and examinations of the efficacy of mindfulness interventions are among the key theoretical knowledge bases from which the field of mindfulness is derived. The content analysis demonstrated the beneficial effects of mindfulness meditation for physical and mental health conditions. The bibliographic coupling revealed novel directions in cognitive behavioral therapy, emotion regulation, the application of mindfulness practice to children and adolescents, mindfulness at work, and the role of mindfulness in positive psychology. The large sample of articles that was analyzed allowed us to provide a broader and more objective overview than possible with other forms of literature reviews. The combination of the three bibliometric techniques granted deeper insights into the complex multidisciplinary field of mindfulness, along with specific suggestions for future research.